PENGARUH KUALITAS PELAYANAN PRAMUWISATA MANDARIN TERHADAP TINGKAT KEPUASAN WISATAWAN CINA YANG BERKUNJUNG DI DAYA TARIK WISATA PURA ULUWATU, KUTA SELATAN BADUNG - Anindya Putri Lestari; I Ketut Suwena; I Nyoman Sudiarta (Jurnal IPTA (Industri Perjalanan Wisata), 2016)
This research is aimed at to know the positive influence on the quality of service guides to tourist satisfaction mandarin Chinese. Sample in this study were 105 respondents using purposive sampling technique. Data collection techniques used were observation, questionnaire, interview, and literature study. Data were analyzed using analysis of Likert scale, validity, reliability, classical assumption (normality test, multicoloniarity test, heteroscedasticity test), multiple linear regression analysis (t test and f), the analysis of correlation and coefficient of determination. The result of analysis shows the fifth factor research (tangibles, empathy, reliability, responsiveness, assurance) has a positive influence and significant to satisfaction rating of 51.2%. The test results of multiple linear regression analysis states that variable reliability has a positive coefficient 3,599 and greater influence to the satisfaction of Chinese tourists who visit the tourist attraction Uluwatu South Kuta Badung.